Mengasah Kreativitas Siswa SD Negeri 1 dan 5 Karangrowo melalui Pembuatan Poster Bertema Pancasila menggunakan Aplikasi Digital Canva - Zaenab Isnaini; Izzatul Aliyah; Muhammad Luthfan Hawali; Dzulrifaad Ubaidillah Al Afza; Rossi Galih Kesuma; Maulana Achmad Dhani; Helfi Julia; Yuliana Ainur Habibah; Danica Herminia Santana; Yulinda Putri Rahmaningrum; Kesya Adinda Putri; Septya Hanung Pramudya (FKIP, Universitas Palangka Raya, 2024)
This activity helps elementary school students in Indonesia learn digital literacy, critical thinking, creative thinking, and collaboration by making Pancasila-themed posters with the Canva app. The activity trained and mentored 5th graders from two schools in Kudus in using Canva to create posters. The activity had phases for planning, implementation, and evaluation. The training improved students' understanding of digital literacy, technical skills, creativity, speaking skills, motivation, and appreciation. It also increased their interest in technology and improved their skills and motivation in learning. This shows that integrating educational technology into learning can be effective for enhancing student skills and motivation. The activity aimed to address the issue of low digital literacy among elementary school students in Indonesia and improve their abilities through poster making using Canva.